SOCIAL RESPONSIBILITY AND ETHICS IN THE BANKING BUSINESS: MYTH OR REALITY? A CASE STUDY FROM SLOVAK REPUBLIC - Belás, Jaroslav (Economic Annals, 2012)
The aim of this article is to examine the social context of the banking business and to define the basic attributes of corporate social responsibility and ethics in commercial banking. One part of the presents the results of the author’s empiric research into the moral attitudes of bank employees in the Slovak Republic. The importance of ethical standards for financial markets is based on the purpose of commercial banks and other financial institutions, which operate with the money of others. The financial crisis has revealed other significant economic implications, and the considerable lack of moral values in commercial banking has been reflected in bankers’ unscrupulous approach to their clients. The crisis has also caused a fundamental turnaround in public opinion towards commercial banking and has increased the pressure to apply moral principles, which represent an appropriate complement to banking regulation. The results of our research show a low level of employee loyalty in the banking sector of the Slovak Republic. This paper can serve as an inspiration for future economic and sociological research by emphasizing the fact that pursuit of profit can be compatible with added social value.